2011 6th IEEE Conference on Industrial Electronics and Applications 2011
DOI: 10.1109/iciea.2011.5975776
|View full text |Cite
|
Sign up to set email alerts
|

Exactly analysis of ZVS behavior for class E inverter with resonant components varying

Abstract: Class E resonant power amplifier (or inverter) is often applied to design a high frequency switching power converter. The zero voltage switching (ZVS) or zero current switching (ZCS) operation leads the converter to high converting efficiency even the converter works at high frequency. Theoretically, with a high speed power transistor, the class E amplifier can work from several megahertzes to dozen of megahertzes. While the resonant components of class E inverter are varying, the ZVS operation will be shiftin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The total losses will be P total = P cond + P on + P off (30) From (28) and (29), it is concluded that the total switching losses in the system is 24.84 W. In the overall system, the DC-DC efficiency is 86.45% at 0.16 coupling. This efficiency is maintained more or less throughout the coupling range from 0.1 to 0.3 in the proposed system.…”
Section: Switching Lossesmentioning
confidence: 99%
See 1 more Smart Citation
“…The total losses will be P total = P cond + P on + P off (30) From (28) and (29), it is concluded that the total switching losses in the system is 24.84 W. In the overall system, the DC-DC efficiency is 86.45% at 0.16 coupling. This efficiency is maintained more or less throughout the coupling range from 0.1 to 0.3 in the proposed system.…”
Section: Switching Lossesmentioning
confidence: 99%
“…However, turn on switching losses will occur. To reduce the turn on losses, diode followed by capacitor combination is connected across the switch [27, 28]. The conventional ZVS switching has reduced the turn on switching losses by 85%.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…Analysis of the ZVS drifting and the variations of circuit behaviour while the circuit components are varying were proposed in [5, 16]. In these literatures, an exact circuit model in frequency domain was proposed to analyse the ZVS behaviour of the class E inverter.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing the study on the class E inverter design, in this paper, we focus on an active ZVS tracking controller design based on the concepts of tuning the switching frequency and the analysis of ZVS conditions in [16]. By analysing the correlation of realistic shifting angle and the optimal shifting angle of load current, in this paper, a searching procedure for the optimal switching frequency is proposed to decide the operation frequency for the practically class E inverter designing.…”
Section: Introductionmentioning
confidence: 99%
“…Tu and Toumazou [4] designed a class E amplifier on integrated circuit with 1.8 GHz resonant frequency. Various topologies have appeared to expand the applications of class E circuit such as class E inverter [3,[5][6][7][8][9][10][11][12], class E DC/DC converter [5,13,14] and class E rectifier [7]. Also, the class E circuits are applied to RF power amplifier [4,15], induction heating system [11,15,16] and RF powering [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%